VEGF is a modifier of amyotrophic lateral sclerosis in mice and humans and protects motoneurons against ischemic death - Lambrechts, Diether; Storkebaum, Erik; Morimoto, Masafumi; Del-Favero, Jurgen; Desmet, Frederik; Marklund, Stefan L; Wyns, Sabine; Thijs, Vincent; Andersson, Jörgen; van Marion, Ingrid; Al-Chalabi, Ammar; Bornes, Stephanie; et al. (Nature genetics, 2003)
Amyotrophic lateral sclerosis (ALS) is an incurable degenerative disorder of motoneurons. We recently reported that reduced expression of Vegfa causes ALS-like motoneuron degeneration in Vegfa δ/δ mice. In a meta-analysis of over 900 individuals from Sweden and over 1,000 individuals from Belgium and England, we now report that subjects homozygous with respect to the haplotypes −2,578A/−1,154A/−634G or −2,578A/−1,154G/−634G in the VEGF promoter/leader sequence had a 1.8 times greater risk of ALS ( P = 0.00004). These 'at-risk' haplotypes lowered circulating VEGF levels in vivo and reduced VEGF gene transcription, IRES-mediated VEGF expression and translation of a novel large-VEGF isoform (L-VEGF) in vivo . Moreover, SOD1 G93A mice crossbred with Vegfa δ/δ mice died earlier due to more severe motoneuron degeneration. Vegfa δ/δ mice were unusually susceptible to persistent paralysis after spinal cord ischemia, and treatment with Vegfa protected mice against ischemic motoneuron death. These findings indicate that VEGF is a modifier of motoneuron degeneration in human ALS and unveil a therapeutic potential of Vegfa for stressed motoneurons in mice.